Underrepresentation of women in sport leadership: A review of research - Burton, L. J. (Sport Management Review, 2015)
Despite increased participation opportunities for girls and women in sport, they are underrepresented in leadership positions at all levels of sport. The objective of this review is to provide a multilevel examination of available scholarship that contributes to understanding why there are so few women in leadership positions within sport. From a macro-level perspective, scholarship regarding the institutionalized practices of gender in sport is examined. The meso-level review includes stereotyping of leaders, issues of discrimination, and gendered organizational cultures. Finally research reviewed at the micro-level explores women's expectations in leadership positions, occupational turnover intentions, and the influence of symbolic interactionism on women's career advancement. In addition, the author identifies new research areas and additional recommendations for how best to increase the number of women in leadership positions in sport.